Adrenoleukodystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The biochemical and clinical efficacy of dietary erucic acid (C22:1) therapy for X-l inked adrenoleukodystrophy (ALD) was investigated at the Departments of Pediatrics, Human Genetics, Neurology, Medical College of Virginia, Virginia Commonwealth University, Richmond, VA, and the Department of Neurology, University of California, Davis, Sacramento, CA.